Problems of Teaching and Learning in Basic Schools-The Case of Ewusa Demonstration Basic School, Ghana - Anderson, Hans Kweku; Donkoh, Kweku Esia (Advances in Social Sciences Research Journal, 2016)
Education is considered the main vehicle through which nations are developed. This implies that effective teaching and learning in schools should be enforced to ensure that educational and school goals are achieved for national development. The study was therefore conducted at the Ewusa Demonstration Basic School in the Central Region of Ghana with the aim of describing how teaching and learning is done in the school. The method used was qualitative for both the data collection and analysis. Participants for the study were teachers and pupils of the school. The findings from the study were that teaching and learning generally goes on in the school as expected. However, lack of teaching and learning materials, large class size, and poor socio-economic background of the pupils and some aspects of the teacher factor pose threat to effective curriculum implementation in the school. It is, therefore, recommended that teachers of the school should adhere to the Ministry of Education’s (2012) directives on teaching at the basic level. The stakeholders of the school should also provide the basic needs of the school, and the government’s school feeding programme should be extended to the school to enhance enrolment and interest of the children in the town to go to school.